The FACTORS ASSOCIATED WITH CAESAREAN SECTION AT A RURAL HOSPITAL IN SOUTH WESTERN UGANDA: A CROSS-SECTIONAL STUDY - Lilian Nuwabaine; Mathius amperiize; Patience Annet Nakalega (Student's Journal of Health Research, 2023)
Background:  Globally, the overall prevalence of caesarean section (CS) is estimated at 18.6%, with 27% in high-income countries and 6% in low- and middle-income countries. There is an increase in trends of CS in Uganda from 8.5% in 2012 to 11% in 2016. No studies have been carried out to account for the high rates of CS at Kisiizi Hospital in Uganda. This study determined the proportion and factors associated with CS delivery at a rural hospital in southwestern Uganda. Methods:  This was a cross-sectional study of 321 immediate postnatal women in a rural hospital in southwestern Uganda. A structured questionnaire and data abstract forms were used to collect information on the proportion and factors associated with CS. Eligible participants were enrolled consecutively. Logistic regression analysis was done to identify the factors associated with CS taking into account potential confounders. Results:  This study recruited 321 women with a mean age of 25.8 ± 6.086 years, mean parity of 2.6 ±1.673 and mean antenatal care visits of 4.27 ± 1.197. The proportion of CS in this study was 38.3% (123/321). Of these, 110 (89.4%) were emergencies and 27(10.6%) were electives. Only 8.4% of the respondents were referrals. The commonest indications of CS were fetal distress (28.5%), history of previous CS (18.7%), and poor progress of labour (11.4%). No factors were significantly associated with CS in this study. Conclusion:  There is a high proportion of CS at Kisiizi Hospital in Uganda and this is three times higher than the WHO-recommended CS rates. The majority of CS are emergencies due to fetal distress and poor progress of labour. There is a need for additional studies exploring the reasons for the much higher-than-expected CS rates.